2010
DOI: 10.3390/s101009053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Method for Characterizing Electrical Steel Sheets in the Normal Direction

Abstract: This paper proposes an experimental method to characterise magnetic laminations in the direction normal to the sheet plane. The principle, which is based on a static excitation to avoid planar eddy currents, is explained and specific test benches are proposed. Measurements of the flux density are made with a sensor moving in and out of an air-gap. A simple analytical model is derived in order to determine the permeability in the normal direction. The experimental results for grain oriented steel sheets are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The additional windings (15 turns around each stack of samples) allow using the Hopkinson's law. Various validations of the methodology and results of characterization μ z were made in previous articles [8,9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional windings (15 turns around each stack of samples) allow using the Hopkinson's law. Various validations of the methodology and results of characterization μ z were made in previous articles [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…It requires supposing that there is no fringing around the air gap and that the flux is uniform in it. The authors checked these two assumptions in [8] and they have validated them.…”
Section: Methods For Determining the Normal Permeability Of An Electrimentioning
confidence: 99%
See 1 more Smart Citation
“…We have adopted the recommendation of [31], which considers the relative permeability in the transverse direction as one-third of the one in the rolling direction. The relative permeability in the normal direction (between laminations) was obtained using the calculation procedure given in [32], where the relative permeability, in the normal direction of a set of laminations of grain-oriented silicon steel, was experimentally determined for different magnetic flux densities. It was found that for the point defined by 25 000 A/m and 1.3 T, in the normal direction of the laminations, corresponds to 41.4.…”
Section: -D Fe Simulationsmentioning
confidence: 99%
“…The method is based on the use of direct excitation current in order to eliminate the presence of eddy currents and thereby avoid distortions in the measurement caused by these currents. The measuring system was built so that the magnetic flux was perpendicular to the sample surface (Kato et al , 2009; Hihat et al , 2011, 2010). As the flux does not change in time, in order to generate a required electromotive force, the search coil is continuously being moved in and out of the air gap with a constant velocity v. The movement is perpendicular to the principal direction of the flux density.…”
Section: Introductionmentioning
confidence: 99%